A different perspective on the correlation between histopathological type and PET-CT SUVmax in non-small cell lung cancer: A retrospective cohort study - Yıldız, Özgur Ömer; Aytekin Çelik, İlknur (Journal of Surgery and Medicine, 2019)
Aim: In recent years, alternative therapies targeting directly cancer cells and targeted agents have been developed. The aim of this study is to develop a new perspective on alternative therapies on local targets, as identify the correlation between positron emission tomography-computed tomography (PET-CT) SUVmax and histological type of the tumor in non-small cell lung cancers. Methods: This study is based on the retrospective examination of patients who underwent PET-CT for preoperative staging with non-small cell lung cancer between January 2012 and May 2015. Statistical analyses are made between SUVmax values and histopathological types. Results: The study is including 448 patients who underwent surgery for non-small cell lung cancer. The average size of the mass was 4.5 cm and the average SUVmax value was calculated as 13.3. The patients were classified into five groups according to their histopathological diagnosis. PET-CT fluorodeoxyglucose (FDG) involvement has been classified for different histopathological types. Statistically significant correlation was identified between the tumor size and histopathological diagnosis. It was found that the difference between SUVmax values of the adenocarcinoma tumors and other types are found statistically significant. SUVmax values have been found mostly between 5-10 in patients with adenocarcinoma and 10-15 in others. Conclusion: Considering that there are statistically significant differences between PET-CT SUVmax values of tumor cell types, we argue that radiopharmaceuticals which could provide different and local treatment should be used in cancer treatment, they should be combined with alternative therapies such as loco-regional treatment methods, and the studies in that direction should continue in line with the technological developments.